EFL STUDENTS’ DIFFICULTIES IN UNDERSTANDING WORD MEANING WHEN READING NARRATIVE TEXTS - Aliq Devan Arinal Haq; Kushardiyanti Novinda (Universitas PGRI Palembang, 2026)
Reading proficiency plays a crucial role in enabling English as a Foreign Language (EFL) learners to comprehend academic texts effectively. However, vocabulary comprehension remains a significant challenge for many learners. While numerous studies have examined vocabulary-related difficulties, limited research has focused on Indonesian twelfth-grade students. This study investigates the experiences and perceptions of twelfth-grade EFL learners at SMA N 12 Semarang regarding the challenges they encounter in understanding word meanings while reading narrative texts. A qualitative descriptive design was employed. Data were collected through questionnaires administered to 34 students from one intact class and were further supported by semi-structured interviews with one English teacher and six students. The findings revealed that learners experienced various lexical difficulties, including unfamiliar vocabulary, idiomatic expressions, polysemous words, grammatical variations, and lengthy complex sentences. These challenges were influenced by limited vocabulary exposure and affective factors such as frustration. To overcome these difficulties, students primarily relied on digital translation tools, particularly Google Translate, and collaborative discussions with peers. The study highlights the need for instructional strategies that enhance vocabulary development and reading comprehension skills among EFL learners.